The crystal structure of dimethyl 2,2ʹ-((adamantane-1,3-diylbis(4,1-phenylene)) bis(oxy))diacetate, C28H32O6 - Chen Xiao-Ming; Zeng Fei (Zeitschrift für Kristallographie - New Crystal Structures)
C28H32O6, orthorhombic, Pnma (no. 62), a = 7.752(2) Å, b = 29.959(8) Å, c = 10.176(3) Å, V = 2363.5(11) Å3, Z = 4, R gt(F) = 0.1145, wR ref(F 2) = 0.1076, T = 296(2) K.